River basin management and fiscal decentralisation: mutually supportive or counterproductive? A case study of Mongolia - Ines Dombrowsky; Ariunaa Lkhagvadorj; Mirja Schoderer (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
In the last decade, Mongolia has undergone parallel processes of institutionalising River Basin Organisations (RBOs) and of fiscal decentralisation. River basin management calls for managing water resources at the river basin level in order to promote a sustainable resource use. However, often RBOs remain underfunded. Fiscal decentralisation involves shifting certain fiscal responsibilities to lower levels of government. Against this background, the paper asks whether fiscal decentralisation supports or counteracts river basin management in the Mongolian case. The paper finds that at the sub-national level, a high number of actors are involved in water governance. Despite a broad division of labour, a high level of overlap exists in terms of data management; monitoring water resources, water uses and law implementation; law enforcement; and to a certain degree the implementation of measures among these actors. In terms of financing water governance, River Basin Authorities (RBAs) are primarily financed through the national budget and Aimag (province-level) Environmental Authorities (AEAs) through sub-national province budgets. However, uncertainties exist regarding the allocation of water-use fees. In practice, available funds to RBAs only cover fixed costs. AEAs have somewhat higher budgets, but do not necessarily use these funds for water-related projects or earmark water-use fees. Inconsistent legal provisions on water-use fees have led to competition between AEAs and RBAs, but also to first collaborative arrangements. We conclude that in Mongolia, fiscal decentralisation and river basin management are, so far, hardly mutually supportive and recommend a number of legal and financial adjustments. Key words: River basin management, fiscal decentralisation, funding water governance, water use fees, Mongolia
Keywords: 330; Governance; Wasser